Efficiency of a dye-sensitized photoelectrochemical device using thionine and triturated zinc oxide at different potency. Issue 22 (16th November 2016) - Bandyopadhyay, Poonam; Chakraborty, Sweta; Basu, Ruma; Das, Sukhen; Bhar, Durga Shankar; Manchanda, Rajkumar; Khurana, Anil Kumar; Nayak, Debadutta; Nandy, Papiya
ABSTRACT: A new and novel material, triturated zinc oxide nanoparticles, which is eco-friendly, easily available, low in cost, has been used here for the first time for enhancement of photovoltage generation and efficiency of a dye-sensitized photoelectrochemical device. This material when diluted and strongly agitated, together termed as potentized, is used as nanomedicine for centuries. This study using this material at two different potencies (6C and 30C) shows that addition of this material to thionine dye of concentration 0.85 μM enhances photovoltage generation significantly. The efficiency obtained with the latter is 0.41%, whereas it is 0.003% with dye only.